Free patent titling program : its impact on the sustainability of beneficiaries in Ilocos Norte - Abitong, Oliva T. (Laoag City, Ilocos Norte : [s.n.], 2005)
This study determined the impact of the free patent titling program (FPTP) on the sustainability of the beneficiaries in Ilocos Norte, calendar year 2003. The descriptive-analytical method of research was used while the questionnaire was utilized to elicit the responses of the respondents. The study found that the FPTP was very well implemented and highly sustainable to the beneficiaries. the beneficiaries and implementers significantly differed in their perceptions on the level of implementation and sustainability, the profile of the beneficiaries were not related to program implementation while the educational attainment and family size are related to some variables of sustainability. the FPTP had a significant impact on the sustainability of the program to the beneficiaries.
Bibliography: pages 114-116.
CHED-La Union
Keywords: Land grants